Microbial keratitis following accelerated corneal collagen cross-linking - Shreesha Kumar Kodavoor; Nikit J Sarwate; D Ramamurhy (Oman Journal of Ophthalmology, 2015)
A deep stromal infiltrate with hypopyon appeared in central cornea of right eye of a 15-year-old boy postoperatively after 2 days, who underwent uneventful accelerated corneal collagen crosslinking (C3R) with riboflavin and ultraviolet-A (UVA) for the treatment of keratoconus. Staphylococcus aureus keratitis was confirmed by the microbiological studies, which guided intense treatment with topical and systemic antibiotics. Before C3R, the best corrected visual acuity (BCVA) in the ocular dexter was 20/30 with the refraction of − 1.00 DS/−5.00 DC × 30° with drop to 20/400 following the infection. After intensive treatment BCVA recovered to 20/40 with the refraction of −4.0 DC × 60° at 6 months postprocedure. Slit lamp examination at this stage revealed a faint nebulo-macular grade scar in the central cornea involving visual axis. Collagen crosslinking with riboflavin-UVA is a minimally invasive method, but traditionally requires epithelial removal, which could be a predisposing factor to bacterial keratitis.